Optimasi Panjang Mainroll pada Industri Pulp & Paper untuk Kebutuhan Kertas HVS dengan Integer Programming - Silalahi, Agustinus; Hidayat, Trifenaus Prabu; Hutahaean, Hotma Antoni; Suwasto, Febian (Metris: Jurnal Sains dan Teknologi, 2024)
PT. XYZ is a company engaged in the production of paper and pulp. These are two products are interrelated because to produce paper, raw materials are neededin the form of pulp. And often the paper production in the factory is excessive. This study aims to determine the optimal mainroll length according to demand so that overproduction will be minimized. The approach used is Integer Programming with the Branch and Bound method, where previously obtained combinations of possible paper arrangements on the mainroll with a maximum length of 80 km and a the width of 8,5 m. based on the optimal calculation results for the December 2022 production period, the mainroll length produced is 139,23 km which produced 14.891 reams for A4 paper, 10.539 reams for F4 paper and 10.239 reams for Q4 paper. The excess production of each type of paper was 0.34 %, 0,02 % dan 1,82 %, respectively. While the total overproduction for all types of paper sizes was 0,67 %. Production results in December 2022, overproduction of A4, F4 and Q4 were 1,15 %, 3,26 % and 2,92 %, respectively. While the total overproduction for all types of paper sizes was 2,28 %. The standart deviation of the calculation of real conditions is 1,13%, meaning that the deviation of excess production in real conditions is greater.